: Desenvolvimento de um programa em python para análise estrutural de pórticos planos isostáticos pelo método das seções - Oliveira, João Marcos Azevedo de (Universidade Federal Rural do Semi-Árido, 2019)
Graphical computer programs that present instantaneous results and better visualization, become great allies in the field of construction, allowing complex structures to be better analyzed. The use of computer programs was also inserted in teaching-learning, helping students in the behavior of structures. The idea of studying is one of the approaches aimed at the development of software using a Python language, which makes it possible for patients to analyze in isostatic flat plans. For software validation, three examples have been tested. The first test was a simple classic with triangular distributed distribution, the second was a simple simple with the distribution evenly distributed by an inclined element, both copies found in the literature of the branch of the structural analysis, is already available in parameters of one structure with real behavior. The process of entering data by the user and solving practical problems, the certification program, compliance with data in terms of results, the presentation of an efficient tool, the provision of solutions quickly and easily, which makes it possible to interpret the results from a calculation report.
Monografia
Keywords: Esforços internos; Ftool; Programação computacional; Relatório; ENGENHARIAS::ENGENHARIA CIVIL